PROCESS SAFETY AND ENVIRONMENTAL MANAGEMENT PLANNING IN THE AUTOMATIC MELTING PROCESS AT PT SOLDER BAR X - Rizky Ernando; Marningot Tua Natalis Situmorangama (RADJA PUBLIKA, 2025)
A metal industry company such as PT Solder Bar X has significant potential hazards and environmental impacts in its production process, particularly during the automated melting stage. This study aims to develop an integrated process and environmental safety management plan in accordance with the principles of Process Safety Management (PSM) and the ISO 14001:2015 Environmental Management System. The methodology used includes hazard and environmental aspect identification, risk assessment using the Hazard Identification, Risk Assessment and Determining Control (HIRADC) method, and assessment of the significance of environmental aspects. Data were collected through production process observations, company documents, and recent literature studies (2020–2024). The identification results indicate several major potential hazards, such as molten metal spills, heat exposure, metal particulate emissions, and solid and liquid waste from the cooling process. Based on the HIRADC assessment, high risks were identified in molten metal handling activities and the ventilation system. Significant environmental aspects lie in air emissions and waste management. The control plan includes engineering controls, ventilation system improvements, implementation of standard operating procedures, and strengthening employee training programs. The integration of PSM and ISO 14001 has been proven to provide a systematic approach to controlling hazards while maintaining environmental performance. This research can serve as a reference for similar industries in developing comprehensive safety and environmental management systems.